Scran: Scotland's history and culture website 20 years on. (March 2017) - James, Andrew
Abstract : Scran (www.scran.ac.uk ), a service of Historic Environment Scotland, is the leading source for copyrightcleared images, videos and sounds from over 300 galleries, museums and archives. Its subscribers include colleges, schools, universities, libraries and individuals. It was established 20 years ago, and has grown and developed as the internet has evolved. As it enters its third decade, it must face up to a challenging digital landscape in which users' expectations of searching for, reusing and sharing digitized materials is shifting and changing.